Analysis of Nasal Septal Deviation in Cleft Palate and/or Alveolus Patients Using Cone-Beam Computed Tomography. (August 2014) - Jiang, Meng; You, Meng; Wang, Shuai; Wang, Ke; Feng, Bin; Wang, Hu
Objective: This study was performed to analyze features of nasal septal deviation of patients with different cleft types and noncleft controls. Study Design: Case-control study. Setting: West China Hospital of Stomatology, Chengdu, China. Subjects and Methods: Sixty-six patients with palatal and/or alveolar cleft and 42 noncleft controls were recruited in the study. All the subjects have undergone cone-beam computed tomography scan. The range, angle, vertical location, and convex direction of nasal septal deviation were carefully studied for each subject. The data were compared between the cleft group and noncleft controls. The differences of deviation among various cleft types were also carefully evaluated to demonstrate whether the differences in cleft types affect the features of nasal septal deviation. Results: The mean range 7.71 mm and angle 10.37° of nasal septal deviation in cleft group were significantly greater than that in control group of 1.96 mm and 2.34°. The maximum point of nasal septal deviation in cleft group vertically occurred more often at inferior turbinate level (27/66) followed by lower inter-turbinate level (16/66) and middle turbinate level (11/66). Patients with complete cleft palate presented greater deviation than incomplete cleft palate or simple cleft alveolus patients. The convex direction of deviation was to the cleft side for all patients with complete cleft palate or simple alveolar cleft. Conclusion: Patients with cleft palate and/or alveolus presented greater deviation of nasal septum than noncleft controls. Patients of different cleft types showed various severity and features of nasal septal deviation.